Comprehension and risk elicitation in the field: Evidence from rural Senegal - Charness, Gary; Viceisza, Angelino (International Food Policy Research Institute, 2011)
In the past decade, it has become increasingly common to use simple laboratory games and decision tasks as a device for measuring both the preferences and understanding of rural populations in the developing world. This is vitally important for policy implementation in a variety of areas. In this paper, we report the results observed using three distinct risk elicitation mechanisms, using samples drawn from the rural population in Senegal, West Africa. Whatever the intellectual merits of a particular elicitation strategy, there is little value in performing such tests if the respondents do not understand the questions involved. We test the understanding of and the level of meaningful responses to the typical Holt-Laury task, to a simple binary mechanism pioneered by Gneezy and Potters in 1997 and adapted by Charness and Gneezy in 2010, and to a nonincentivized willingness-to-risk scale a la Dohmen et al. We find a disturbingly low level of understanding with the Holt-Laury task and an unlikely-to-be-accurate pattern with the willingness-to-risk question. On the other hand, the simple binary mechanism produces results that closely match the patterns found in previous work, although the levels of risk-taking are lower than in previous studies. Our study is a cautionary note against utilizing either sophisticated risk-elicitation mechanisms at the possible cost of seriously diminished levels of comprehension or nonincentivized questions in the rural developing world.